Genetic Diversity Assessment of Luffa aegyptiaca Landraces Endemic in Egypt Based on Some Molecular Markers - Al Tahlawy, Mohammad Abdel Sttar; Ibrahim, Mahmoud Abdel Aziz; Matter, Mohamed Ahmed; Mohamed, Mervat El Sayed; Sakr, Mahmoud Mohamed (Plant Tissue Culture and Biotechnology, 2016)
Luffa aegyptiaca is a popular climbing herb endemic in Egypt. We studied the genetic diversity among ten Luffa landraces (Cairo, Beni Suef, Menoufiya, Damietta, Banha, Aswan, Kafr el?Sheikh, Bir el?Abd, MarsaMatruh and Asyut) collected from different districts in Egypt. The results obtained from DNA fingerprinting revealed that there were polymorphic loci with average percentage of 44.6 among collected landraces whereas polymorphic loci obtained from SDS?PAGE were 23%. Discrimination between landraces was more efficient by using RAPD?PCR marker than total proteins SDS?PAGE which showed a limited level of intraspecific diversity. Plant Tissue Cult. & Biotech. 26(2): 209-217, 2016 (December)